Kinerja Aparatur Sipil Negara (ASN) Ditinjau Dari Aspek Hukum Administrasi Negara - Hartal Deskayanto Sura; Firman Umar; Andi Aco Agus (Jurnal Tomalebbi, 2025)
Performance of Civil Servants Reviewed from the Perspective of State Administrative Law at the Ariang Sub-district Office, Makale District, Tana Toraja Regency. Thesis, Pancasila and Citizenship Education Study Program, Department of Civic Education and Business Law, Faculty of Social and Law Sciences, Makassar State University, Supervised by Imam Suyitno and Herman. This research aims to determine: (1) The performance of civil servants at the Ariang Sub-district Office in Makale District, Tana Toraja Regency, reviewed from the perspective of legal certainty. (2) The performance of civil servants at the Ariang Sub-district Office in Makale District, Tana Toraja Regency, reviewed from the perspective of justice and equality. (3) Obstacles in the application of the principles of legal certainty and justice and equality at the Ariang Sub-district Office in Makale District, Tana Toraja Regency. This type of research is qualitative research with a descriptive approach. The sources of this research are the Sub-district head and employees. Data collection techniques include observation, interviews, and documentation. Data validity checking is done using data source triangulation techniques. The results of the research show that: (1) The performance of Civil Servants at the Ariang Sub-district Office in Makale District, Tana Toraja Regency, is considered good from the perspective of legal certainty. Complete legal documents, consistency in the application of administrative legal procedures, and the level of compliance of Civil Servants with applicable legal regulations are the main indicators showing the quality of ASN's performance is quite good. (2) The performance of Civil Servants at the Ariang Sub-district Office in Makale District, Tana Toraja Regency, can be considered good from the perspective of justice and equality. ASN has shown consistency in providing fair services to all residents without discrimination, as well as openness to inputs and aspirations of the community in policy development. (3) The Ariang Sub-district Office in Makale District, Tana Toraja Regency, faces obstacles in applying the principles of legal certainty and justice and equality. The main focus is on the clarity and openness of legal information that is not accessed by the community, as well as consistency in empowering community participation. Improvement efforts include providing easily accessible legal information, increasing public legal awareness, and better coordination among related institutions. The hope is that with these steps, obstacles in the application of legal and justice principles can be overcome for better services to the community.